Long-term metabolic effects of non-nutritive sweeteners - Moran Rathaus; Loziana Azem; Rinat Livne; Sophie Ron; Idit Ron; Rotem Hadar; Gilat Efroni; Amnon Amir; Tzipi Braun; Yael Haberman; Amir Tirosh (Elsevier, 2024)
Objective: Excessive consumption of added sugars has been linked to the rise in obesity and associated metabolic abnormalities. Non-nutritive sweeteners (NNSs) offer a potential solution to reduce sugar intake, yet their metabolic safety remains debated. This study aimed to systematically assess the long-term metabolic effects of commonly used NNSs under both normal and obesogenic conditions. Methods: To ensure consistent sweetness level and controlling for the acceptable daily intake (ADI), eight weeks old C57BL/6 male mice were administered with acesulfame K (ace K, 535.25 mg/L), aspartame (411.75 mg/L), sucralose (179.5 mg/L), saccharin (80 mg/L), or steviol glycoside (Reb M, 536.25 mg/L) in the drinking water, on the background of either regular or high-fat diets (in high fat diet 60% of calories from fat). Water or fructose-sweetened water (82.3.gr/L), were used as controls. Anthropometric and metabolic parameters, as well as microbiome composition, were analyzed following 20-weeks of exposure. Results: Under a regular chow diet, chronic NNS consumption did not significantly affect body weight, fat mass, or glucose metabolism as compared to water consumption, with aspartame demonstrating decreased glucose tolerance. In diet-induced obesity, NNS exposure did not increase body weight or alter food intake. Exposure to sucralose and Reb M led to improved insulin sensitivity and decreased weight gain. Reb M specifically was associated with increased prevalence of colonic Lachnospiracea bacteria. Conclusions: Long-term consumption of commonly used NNSs does not induce adverse metabolic effects, with Reb M demonstrating a mild improvement in metabolic abnormalities. These findings provide valuable insights into the metabolic impact of different NNSs, aiding in the development of strategies to combat obesity and related metabolic disorders.